Cloud tools and digital competencies in teachers at the University of Huanuco, Peru - Lopez de la Cruz, Edgardo (2023)
Objective. The study aimed to apply cloud-based tools to determine the levels of digital competencies of teachers at the University of Huanuco, Peru. Methods. The study was framed within the framework of applied research, under the experimental method and quasi-experimental design. The population consisted of 663 teachers at the University of Huanuco and the sample consisted of 244 teachers. A structured survey questionnaire was used, which was applied before and after the application. A parametric test was applied to test the main hypothesis and determine whether there was an improvement in the digital competencies of teachers. Results. The results obtained confirm that there was an improvement in digital competencies through the application of the cloud tools and through the training workshops conducted. 63% of teachers obtained a medium level of mastery of digital competencies and 36% achieved a high level; all this in the dimension "informatization and literacy", being one of the most important dimensions. In the other dimensions there was also an increase; for example, in the dimension "information security" 74 % of the teachers achieved a high level. Conclusions. It is concluded that the teachers of the University of Huanuco improved their digital competencies through the use of cloud tools thanks to the virtual training workshops programmed.